2021
DOI: 10.3389/fonc.2021.630417
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Immunological Role of mRNA ac4C Regulator NAT10 in Pan-Cancer: New Territory for Cancer Research?

Abstract: BackgroundNAT10 (also known as human N-acetyltransferase-like protein) is a critical gene that regulates N4-acetylcytidine formation in RNA, similar to the multiple regulators of N6-methyladenosine. However, the underlying functions and mechanisms of NAT10 in tumor progression and immunology are unclear.MethodsIn this study, we systematically analyzed the pan-cancer expression and correlations of NAT10, using databases including Oncomine, PrognoScan, GEPIA2, and Kaplan-Meier Plotter. The potential correlations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…NAT10 also participates in modifying different types of RNA in the nucleolus, including the splicing of precursor rRNA at positions A0, A1 and A2 in yeast 22 . According to the most recent report, the high expression of the mRNA ac4C writer NAT10 indicates poorer prognosis of various malignancies and NAT10‐mediated ac4C modification on mRNA promotes gastric cancer metastasis and EMT 25 . Although NAT10‐mediated modification of ac4C peaks on RNA and proteins has been elucidated, knowledge about the role of ac4C on mRNA and its regulatory networks in cancer remains intricate to this day.…”
Section: Introductionmentioning
confidence: 99%
“…NAT10 also participates in modifying different types of RNA in the nucleolus, including the splicing of precursor rRNA at positions A0, A1 and A2 in yeast 22 . According to the most recent report, the high expression of the mRNA ac4C writer NAT10 indicates poorer prognosis of various malignancies and NAT10‐mediated ac4C modification on mRNA promotes gastric cancer metastasis and EMT 25 . Although NAT10‐mediated modification of ac4C peaks on RNA and proteins has been elucidated, knowledge about the role of ac4C on mRNA and its regulatory networks in cancer remains intricate to this day.…”
Section: Introductionmentioning
confidence: 99%
“…More than 100 epigenetic modifications of mRNA, including N6-adenosine methylation (m6A), cytosine hydroxylation (m5C), and N1-adenosine methylation (m1A), have been revealed in mediating the stability, function, and splicing process of targeted mRNAs (9)(10)(11). Previous studies on m6A have reported that two important readers, YTHDF2 and YTHDC1, were respectively located in the nucleus and cytoplasm of oocytes, which played crucial roles in mRNA degradation, transcriptome switching, and selective splicing during oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…This proposal could also be extrapolated to other cancers showing significant correlation with THUMPD1 expression. Distinct from the results of pan-cancer analysis of NAT10, our proposition demonstrates the difference between NAT10 and THUMPD1 in clinical and immunological function, though they both serve as the writing tools of ac4C [ 34 ]. Hence, further studies are required to determine the detailed difference and the possible underlying mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Here, with distinct prognosis in high THUMPD1 expression cohorts, KIRC and LIHC were treated as the representation to support the idea that THUMPD1 may play distinct roles in different cancer types. According to pan-cancer analysis of NAT10, the partner of THUMPD1 for mRNA acetylation, high NAT10 expression is associated with worse survival in LIHC, lymphoma and colorectal cancer [ 34 ]. Although NAT10 and THUMPD1 work synergistically, their effects on prognosis of diverse cancer types are not totally the same.…”
Section: Discussionmentioning
confidence: 99%